The Influence of Profitability, Leverage, Independent Commissioner, and Company Size to Tax Avoidance - Anita Wijayanti, Intan Taqta Alfina, Siti Nurlaela & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to test the influence of profitability, leverage, independentCommissioner, and the size of the company to tax avoidance on mining companieslisted on the Indonesia stock exchange in 2014-2016. The independent variable inthis study is the Retrun On Assets (ROA), Debt To Equity Ratio (DER), theindependent Commissioner, and the size of the company. For the dependentvariable in this study using Cash Effective Tax Rate (CETR). The population thatused as many as 45 companies, research on samples with a purposive samplingtechnique that generates a sample of 10 companies with a three-year period inorder to conduct research. Analytical techniques used were linear regressionanalysis. The results of this research show that leverage, independentCommissioner of the company and the size effect on tax avoidance. Whileprofitability has no effect on tax avoidance.Keywords: Profitability, Leverage, Independent Commissioner, Company Size, TaxAvoidance